Circular RNA Expression in Oral Squamous Cell Carcinoma - Wang, Yu-Fan; Li, Bo-Wen; Sun, Shuai; Li, Xiang; Su, Wen; Wang, Zhi-Hong; Wang, Feng; Zhang, Wei; Yang, Hong-Yu (Frontiers in Oncology, 2018)
Circular RNA (circRNA) is a type of non-coding RNA molecule that affects the cellular regulatory network by sequestering microRNA (miRNA) like a sponge. This study was performed to identify differentially-expressed circRNA in oral squamous cell carcinomas (OSCCs). By high-throughput sequencing, microarray circRNA expression profiles were acquired from patients with OSCCs (n[Please check that this retains your intended meaning.]=8) and controls (n=8), which totaled 1921 existing circRNA molecules[Please check that this retains your intended meaning. RNA itself cannot take a plural form, so something additional is required after.] and 10021 novel circRNA molecules[As above.]. Most of the circular RNA is from exons and distributed in the No. 1 and 2 chromosomes. Eight up-regulated and down-regulated circRNA molecules were identified as differentially-expressed in OSCCs. Among this, the expression of circ_000334, circ_006740 and circ_006371 are significantly down-regulated in 42 pairs of samples, which means that these circRNA molecules might be implicated in oncogenesis and development of OSCCs.